2021
DOI: 10.3390/mi12121469
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility Study of a Commercial Printed Circuit Board for Biomedical Applications: Lab-on-PCB for Organotypic Retina Cultures

Abstract: Printed circuit board (PCB) technology is well known, reliable, and low-cost, and its application to biomedicine, which implies the integration of microfluidics and electronics, has led to Lab-on-PCB. However, the biocompatibility of the involved materials has to be examined if they are in contact with biological elements. In this paper, the solder mask (PSR-2000 CD02G/CA-25 CD01, Taiyo Ink (Suzhou) Co., Ltd., Suzhou, China) of a commercial PCB has been studied for retinal cultures. For this purpose, retinal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Biocompatibility is a key factor for PCB systems intended for biological applications. A few research groups have reported the biocompatibility of several PCB systems for in vitro cell cultures [41,42]. The proposed system has been implemented in a 24-well cell culture plate with Human Dermal Fibroblast (HDF) cell culture to explore biocompatibility.…”
Section: Biocompatibility Analysismentioning
confidence: 99%
“…Biocompatibility is a key factor for PCB systems intended for biological applications. A few research groups have reported the biocompatibility of several PCB systems for in vitro cell cultures [41,42]. The proposed system has been implemented in a 24-well cell culture plate with Human Dermal Fibroblast (HDF) cell culture to explore biocompatibility.…”
Section: Biocompatibility Analysismentioning
confidence: 99%
“…The biocompatibility of this MEA has been demonstrated for cardiomyocyte cultures, large slices, or whole-heart preparations [ 212 ], Figure 17 A. In addition, the biocompatibility of the white solder mask PSR-2000 CD02G/CA-25 CD01 has been checked for a retinal continuous culture system, with good results [ 213 ]. Finally, the double-side copper layer PCB has also been used to fabricate MEAs; for example, the one provided by Ayanda Biosystems (Ayanda Biosystems SA, Lausanne, Switzerland) [ 214 ].…”
Section: Printed Circuit Boards For Biomedical Applicationsmentioning
confidence: 99%
“…The biocompatibility of this MEA has been demonstrated for cardiomyocyte cultures, large slices, or whole-heart preparations [212], Figure 17A . In addition, the biocompatibility of the white solder mask PSR-2000 CD02G/CA-25 CD01 has been checked for a retinal continuous culture system, with good results [213]. Finally, the double-side copper layer PCB has also been used to fabricate MEAs; for example, the one provided by Ayanda Biosystems (Ayanda Biosystems SA, Lausanne, Switzerland) [214].…”
Section: Biosensors and Lab On Pcbmentioning
confidence: 99%